High-Frequency Induction-Heated Combustion Synthesisand Consolidation of Nanostructured NbSi₂ from Mechanically Activated Powders - 김병량; 윤진국; 남기석; 손인진 (한국분말야금학회, 2008)
Dense nanostructured NbSi₂ was synthesized by high-frequency induction-heated combustion synthesis (HFIHCS) method within 1 minute in one step from mechanically activated Nb and Si powders. Highly dense NbSi₂ with relative density of up to 99% was simultaneously synthesized and consolidated under the combined effects of an induced current and mechanical pressure of 60 MPa. The average grain size and mechanical properties (hardness and fracture toughness) of the compound were investigated.